Secure e-transactions using mobile agents with agent broker - Han, Song; Chang, Elizabeth; Dillon, Tharam S. (IEEE, 2005)
This paper presents an e-transactions protocol using mobile agents. However, when mobile agents travel to a number of servers for searching optimal purchase for the underlying customer, the mobile codes should be protected. We integrate a secure signature algorithm with the e-transaction algorithm to maintain the security. In addition, an agent broker is involved in the algorithm that will help to reduce the communications among the mobile agents, the customer, and the servers. We have presented security and privacy analysis for the proposed protocol.